The social identity of the Ukrainian soldier in the conditions of the legal regime of martial law - Serhii A. Mul; Kostiantyn V. Hromovenko (Revista UNISCI, 2023)
The purpose of the article is to study the social identity of the Ukrainian soldier under the legal regime of martial law. The social identity of a Ukrainian soldier under martial law determines his characteristics, perception of his role in society, sense of responsibility to it, and willingness to perform courageous actions in the interests of the country. This essential factor helps to raise the morale and motivation of a soldier in a military conflict. The concept of a soldier's social identity is used on the basis of the analyzed literature and the survey conducted among military personnel. The authors propose and substantiate the thesis that the social identity of a Ukrainian soldier under martial law can be characterized by a sense of commitment to his nation and his essential role in the defense of the country.